BEŞERÎ İDRAK İLE VAHYİN BULUŞMA NOKTASI “Muvâfakat” Fenomeni - Zeliha Bengü Ayata (İslami İlimler Dergisi)
This textis the evaluation/analyze of the phenomenon of approval in regard of the Holy word. Along the view of history; it may be valuable fort he human in quest fort he truth to attitude in a sensible or emotional manner with the sincerity if being a beliver in front of a problem or a difficult situation from the practical world and to be approval of this manner; to be supported; to be allied by the holy message. As it has been studied in regard of historical aspects and with the method of deduction; we can define this work as a quest for an answer to the questions such as what can the phenomenon of approval tell for today’s people , how the holy word seems from its structre constructed within its historical adventure and what is the role of dimensia of human aspect in the reconstruction of the holyword as a text.